Determinants of Behavioral Intention to Use Peer-to-Peer Lending among MSMEs: An Extended UTAUT2 Model Evidence from East Java, Indonesia - Farahiyah Sartika; Nawirah; Ditya Permatasari; Setiani (Universitas Negeri Padang, 2026)
This study aims to analyze the influence of performance expectations, effort expectations, social influence, facilitating conditions, hedonic motivation, price value, habits, and experience on behavioral intention and usage behavior. This study is quantitative research, with a sample of 190 respondents from MSMEs in Malang City, Malang Regency, and Batu City. Using snowball sampling technique, the researcher processed the data with quantitative data analysis technique using a Partial Least Square (PLS) based structural equation model. The results showed that performance expectations had a positive and significant effect on behavioral intention. Social influence has a positive and significant effect on behavioral intention. Facilitating conditions have no effect and are not significant on behavioral intention. Facilitating conditions have no effect on usage behavior. Behavioral intention has a positive and significant effect on usage behavior. Hedonic motivation has a positive and significant effect on behavioral intention. Price value has no effect and is not significant on behavioral intention. Habit has a positive and significant effect on behavioral intention. Experience cannot mediate the relationship between facilitating conditions and behavioral intention. These findings indicate that perceived benefits and behavioral factors play a more prominent role in shaping MSME adoption of P2P lending than operational or infrastructure considerations. This study provides empirical insights for platform providers and policymakers in promoting sustainable access to digital financing for MSMEs.